Bimanual coordination deficits in hands following stroke and their relationship with motor and functional performance - Lai, Chien-Hung (J Neuroeng Rehabil, 2019)
BACKGROUND: Stroke can lead to movement disorders that affect interlimb coordination control of the bilateral upper extremities, especially the hands. However, few studies have investigated the influence of a stroke on bimanual force coordination control between the hands using a quantitative measurement tool, or the relationship of force coordination with paretic upper extremity motor and functional performance. We aimed to investigate these outcomes using a novel measurement device, and analyze the relationship of bimanual force coordination control deficits in both hands with motor and functional performances of the paretic upper extremity in stroke patients. METHODS: Sixteen healthy adults and 22 stroke patients were enrolled. A novel bilateral hand grip measurement device with two embedded dynamometers was used to evaluate the grip force during a bilateral hand grip-force coordination control task. The alternating time and force applied for coordination with the grip force of both hands were calculated to analyze control of bimanual grip force coordination. Motor and functional measurements included the upper-extremity portion of the Fugl-Meyer assessment (FMA-UE), Wolf Motor Function Test (WMFT), Motor Assessment Scale (MAS), and Barthel Index (BI). RESULTS: Compared with the healthy group, the alternating time from the non-paretic to the paretic hand was 27.6% shorter for stroke patients (p < 0.001). The grip force generated for coordination in the healthy group was significantly greater (30–59%) than that of the stroke group (p < 0.05), and the coefficients of variation of alternating time (p = 0.001) and force applied (p = 0.002) were significantly higher in the stroke group than the healthy group. The alternating time from the paretic to the non-paretic hand showed moderately significant correlations with the FMA-UE (r = − 0.533; p = 0.011), the WMFT (r = − 0.450; p = 0.036), and the BI (r = − 0.497; p = 0.019). CONCLUSIONS: Stroke results in a decline in bimanual grip force generation and increases the alternating time for coordinating the two hands. A shorter alternating time is moderately to highly associated with enhanced motor and functional performances.